(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study compares the agreement level between the targeted next generation sequencing assay Deeplex Myc-TB and the LPA and Xpert tests in drug resistant tuberculosis detection using the Cohen’s Kappa coefficient (k). Subject and methods: 100 isolates of drug-resistant Mycobacterium tuberculosis stored at National Lung Hospital having LPA and Xpert rapid test results, and were performed with targeted next genration sequencing using the Deepplex Myc-TB kit. A cross sectional study. Results: Compared to LPA, the agreement level was k = 0.559 for RIF; 0.87-0.91 for INH and FLQ; and 0.48-0.74 for AMK, KAN, and CAP. Compared to Xpert, the agreement level was k = 0.83 for INH; 0.91-0.92 for FLQ and ETH; and 0.74-0.85 for the injectable drugs AMK, KAN, CAP. The targeted next generation sequencing showed almost perfect agreement in detecting FLQ and ETH resistance and very high agreement for INH resistance. Furthermore, it outperformed in not only detecting mutations outside the coverage regions of LPA and Xpert but also in cases of heteroresistance or mixed strains. Conclusion: The targeted next generation sequencing assay for drug resistant tuberculosis detection promises to become an effective tool, providing comprehensive and timely drug susceptibility results to enhance the quality of treatment for drug-resistant tuberculosis.